Reinventing (with) Theory in Rhetoric and Writing Studies : Essays in Honor of Sharon Crowley - Crowley, Sharon, 1943-; Skinnell, Ryan, 1978-; Holiday, Judy; Gerdes, Kendall (Kendall Joy); Alden, Andrea L., 1977- (Book collections on Project MUSE., 2019)
"Scholarship that takes up and extends the practices of inventive theorizing characterized by Crowley's work. Showing that theory is a continual rhetorical process that is indispensable for understanding situations and their potential significance--and a means of persuasion. Includes a foreword, afterword, and interview with Crowley"--Provided by publisher